Chloroplast acetyltransferase GNAT2 acts as a redox-regulated switch for state transitions in tomato - Xiaoyun Wang; Jianghao Wu; Hongxin Li; Ying Liu; Dexian Han; Danhui Dong; Jialong Zhang; Lixin Zhang; Na Zhang; Yang-Dong Guo (Molecular Horticulture)
Abstract State transition is a dynamic process to balance the amount of light energy received by photosystem I (PSI) and photosystem II (PSII) so as to maintain an optimal photosynthetic yield and to minimize photo-damage in a fluctuating light environment. Recent studies show that chloroplast acetyltransferase participates in the acetylation of photosynthetic proteins and state transitions. However, the exact molecular mechanisms are poorly understood. In this study, we characterized a chloroplast acetyltransferase in Solanum lycopersicum, SlGNAT2, and found that mutants lacking this enzyme are deficient in state transitions and retarded in growth under fluctuating light. Acetyltransferase activity assays and fluorescence measurements suggest that 6Lys of mature SlLhcb2 protein is a target of SlGNAT2 and might be involved in state transitions. In addition, 131Cys-related redox changes of SlGNAT2 affect its acetylation activity on SlLhcb2 and influence the assembly of the PSI-LHCI-LHCII supercomplex. Therefore, we propose that the chloroplast redox state may regulate the activity of SlGNAT2 which in turn acetylates SlLhcb2 and mediates state transitions in higher plants.